COMPUTERS AS COGNITIVE MODELS OF COMPUTORS AND VICE VERSA. - Meunier, Jean Guy (Epistemologia, 2013)
According to the dominant formal model in cognitive sciences, cognitive operations are computational and the brain mechanisms that enact them are seen as analogous to those of a computer. Such a model has been criticized from different perspectives: for some it lacks semantics, while for others it is a static or inadequate model, even a 'failed program'. But many of these critics are based on an often-oversimplified conception of Turing's original computing machine, whose sole objective was to imitate 'computors', i.e. humans 'calculating with pencil and paper'. Since this first presentation, Turing himself as well as later scholars have contributed to the refining of the computational model behind the functioning of this machine. However, many of these highly technical modifications were left out in the cognitive appropriation of this model. By revisiting Turing's original machine as well as its theoretical developments, the present paper aims to shed new light on the computational issues related to cognitive models.